Anglicisms in Professional Media Discourse: Dynamics, Spelling Practice, Stylistic Transposition - Shulska, Nataliia M.; Kostusiak, Nataliia M.; Zinchuk, Ruslana S.; Kozlova, Tetyana; Koliada, Elina; Musiichuk, Tetiana; Zavarynska, Iryna; Yablonskyi, Maksym; Holub, Yuliia; Shevchuk, Oksana (My University, 2024)
The article presents a study of the functional and stylistic manifestations of English loanwords found in modern journalism. Approaches to the comprehensive analysis of anglicisms in professional media discourse have been developed. Names that appeared in the corporate communication of media workers earlier, as well as the latest borrowings related to the digitalization of modern media, are characterized. The dynamics of foreign language borrowings are clarified, and the main factors of their appearance are indicated: the need to name new realities, the absence of a nominative unit that would convey the full meaning of the definition in the Ukrainian language; a more precise and concise meaning of a foreign lexeme; the use of abbreviated names instead of descriptive phrases in order to save language; subjective perception of a borrowed word as fashionable or better in sound. The tendency to use mainly transliterated or transcribed anglicisms that have undergone lexical-semantic adaptation and graphic adaptation has been revealed. Spelling practice confirms the anormative writing of borrowed tokens, because we often record spelling mistakes. In the course of the analysis of corporate professionalisms, it was established that most often, nouns are represented by morphological feature, while comparatively fewer verbs is observed. The stylistic differentiation of borrowings indicates the presence of both neutral lexemes, which often have the meaning of terms, as well as slangisms and jargonisms. According to the thematic spectrum, eight groups of English-language nominations used in the professional media sphere are distinguished and analyzed: 1) names of sites, social networks, services, search engines; 2) names of new journalistic genres and types; 3) borrowings identifying people who work with the preparation of media content; 4) nominations denoting phenomena and processes related to the writing of news texts and content of websites; 5) anglicisms that serve as constituent parts of the news; 6) foreignisms related to virtual mass media and digitalization of information; 7) names representing the realities of modern television journalism; 8) names related to the reliability and transparency of the information space.
Keywords: anglicisms; media discourse; professional communication; corporate vocabulary; spelling practice; stylistic transposition